2013 IEEE Sixth International Conference on Biometrics: Theory, Applications and Systems (BTAS) 2013
DOI: 10.1109/btas.2013.6712748
|View full text |Cite
|
Sign up to set email alerts
|

Latent fingerprint indexing: Fusion of level 1 and level 2 features

Abstract: Fingerprints have been widely used as a biometric trait for person recognition. Due to the wide acceptance and deployment of fingerprint matching systems, there is a steady increase in the size of fingerprint databases in law enforcement and national ID agencies. Thus, it is of great interest to develop methods that, for a given query fingerprint (rolled or latent), can efficiently filter out a large portion of the reference or background database based on a coarse matching (or indexing) strategy. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Therefore in proposed approach we fixed the penetration rate to 39 % and observed the hit ratio is 96.7 %. The comparison of our result with Yuan et.al [21] proposed approach and Paulino et al [22] is shown in fig.5. From the graph it is clear that we have reach a higher hit rate as compare to other algorithms.…”
Section: B Indexing Results-mentioning
confidence: 51%
See 1 more Smart Citation
“…Therefore in proposed approach we fixed the penetration rate to 39 % and observed the hit ratio is 96.7 %. The comparison of our result with Yuan et.al [21] proposed approach and Paulino et al [22] is shown in fig.5. From the graph it is clear that we have reach a higher hit rate as compare to other algorithms.…”
Section: B Indexing Results-mentioning
confidence: 51%
“…Paulino et al [22]: In their proposed work they have used the fusion of level-1 and level-2 features to improve indexing performance. In their approach firstly, they have performed the encoding of orientation field.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments on NIST SD 27 against a large background database of 240,258 rolled prints achieved a hit rate of 92.7 % at a penetration rate of 40 % (80.7 % at 10 % penetration rate). Alessandra et al indexed latent fingerprints by fusion of levels 1 and 2 features. This method combines the scores on a constrained version of triplet indexing, Minutia Cylinder Code (MCC) indexing, a new OF descriptor indexing technique that uses a hash function, filtering based on singular points, and averaged ridge period comparison.…”
Section: Related Workmentioning
confidence: 99%
“…A number of fingerprint indexing schemes based on all levels of features have been proposed for both full fingerprint and partial fingerprint indexing since 1997. However, the indexing techniques for full fingerprint are not applicable to partial fingerprint identification because the missing parts of a partial fingerprint are simply ignored (considered void).…”
Section: Introductionmentioning
confidence: 99%
“…In [18] Paulino et al, have proposed an indexing approach, primarily for latent fingerprints, which combines multiple, level 1 and level 2 features to filter out a large portion of the background database while maintaining the accuracy of latent matching. Rolled fingerprints are achieved by rolling a finger from nail to nail to capture the complete ridge details of a finger, while plain or slap fingerprints are obtained by pressing a finger onto a flat surface without movement.…”
Section: Fingerprint Indexing Based On Global Featuresmentioning
confidence: 99%